(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Tverezovska N.T., Tarnavska T. V. Understanding the concept of "system" in various fields of scientific knowledge. In the article rassmotreno tolkovanye termyna «system» of various regions in nauchny’h knowledge. Proslezhena story stanovlenyya and Development integrity principle in nauchny’h study. Address the definition of concepts, harakteryzuyuschyh stroenie and functioning systems: element, podsystema, components, communications, goal, structure, the state system, equilibrium, Stability, development, adaptation.